Implementasi Model Usaha Laundry Syariah Di Pondok Pesantren - Nanang Suhendra; Muhammad Tho’in; Sumadi (Jurnal Ilmiah Ekonomi Islam, 2026)
The objectives of this research are to know how the implementation is sharia principle in Islamic Boarding School laundry service and to analyze the concept, implementation, and the benefit of sharia laundry service in boarding school environment. In conducting this research, the researcher applied qualitative research with descriptive approach, observation, and interview with laundry manager and students. The results of this research show that sharia laundry is not only maintaining the cleanliness of clothes, but also provide character education, spiritual formation, and economic development of pesantren. The conclusion, sharia laundry can be a practical and strategy solution for creating a clean, healthy, and religiously appropriate environment within a pesantren.